An exploration of ball screen effectiveness on elite basketball teams - Vaquera A.; Garcia-Tormo, J. V; Ruano, M. A.; Gomez Morante, J. C (International Journal of Performance Analysis in Sport, 2016)
Performance analysis in basketball is trying to find which factors influence during games and which ones are the key determinants on the game outcome. In this way, ball screens are one of the most important finishing actions during team-tactical plays. The aim of this work was to analyse the ball screen effectiveness according to the contextual factors of elite basketball teams. The sample was composed of 668 ball screens registered from 17 games of the Spanish professional basketball league. The dependent variable of the study was ball screens effectiveness while the independent variables were "offensive system", score-line, court zones, possession duration, and game quarter. The results from the binomial logistic regression reflected the main importance of possession duration and offensive systems as contextual variables that allow modifying the ball screens effectiveness in elite basketball games.